Development and Characterization of HDPE Waste/Ramie Fiber Composites for Geomembrane Applications in Litopenaeus vannamei Shrimp Cultivation - Ahmad Fikri; Ar Razi; Mainisa Mainisa; Arif Fadhilah; Apryza Mila (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Geomembranes are thin geosynthetic materials composed of polymeric layers that function as barriers in direct contact with soil. The properties of HDPE geomembranes suitable for application as vannamei shrimp (Litopenaeus vannamei) aquaculture. HDPE geomembranes applied in vannamei shrimp aquaculture are subjected to thermal loads (UV radiation), oxidative agents, and mechanical force such as interfacial friction and tensile loading in surface wear.  This study aims to improve the mechanical properties of the material by incorporating natural fibers as reinforcement into HDPE–ramie fiber biocomposite. The process of making HDPE–ramie fiber biocomposite uses an single screw extruder with a temperature of 170 oC, a rotation of 20 rpm with a ratio of HDPE waste and ramie fiber of 97.5:2.5, 95:5, and 92.5:7.5. The results of tensile and impact tests show the highest strength and toughness are shown in the HDPE sample and ramie fiber 92.5:7.5 with a value of 5.23 MPa and 96.17 kJ/m2. The highest material ductility was demonstrated in the HDPE and ramie fiber composite 97.5:2.5 with a value of 1.32%. In addition, the highest stiffness was demonstrated in the HDPE and ramie fiber composite 95:5 with a value of 845.40 MPa. The results of the morphological investigation showed that the bond between the matrix and filler was partially formed and the smallest fiber diameter was 4 µm.Keywords: HDPE, Ramie, Composite, Geomembrane, Vanamei